2015
DOI: 10.1097/ta.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative management of hemodynamically unstable abdominal trauma patients with angioembolization and resuscitative endovascular balloon occlusion of the aorta

Abstract: Therapeutic study, level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 11 publications
1
61
0
2
Order By: Relevance
“…The inherent limitations of animal trials highlight the need for further clinical investigations to assess these concerns. Several methods have been developed to mitigate these effects including intermittent balloon deflation (27); Others, being still laboratory focused consist of partial occlusion of the aorta (22) and establishment of an arterial shunt from above to below the balloon (28).…”
Section: Physiological Effects Of the Aortic Occlusion: Proximal And mentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent limitations of animal trials highlight the need for further clinical investigations to assess these concerns. Several methods have been developed to mitigate these effects including intermittent balloon deflation (27); Others, being still laboratory focused consist of partial occlusion of the aorta (22) and establishment of an arterial shunt from above to below the balloon (28).…”
Section: Physiological Effects Of the Aortic Occlusion: Proximal And mentioning
confidence: 99%
“…Survival rates of trauma patients undergoing REBOA from available studies (USA, Japan and Europe) range from 13% to 67% (14)(15)(16)18,20,27,(29)(30)(31)(32)(33)(34). Unfortunately, there are huge discrepancies in methodology, inclusion criteria and interventions.…”
Section: Outcomes Features and Keys For Successmentioning
confidence: 99%
“…Partial inflation with controlled hypotensive target allowed benefits overcome risks of a defective procedure. REBOA adoption, even in a potentially dangerous position, gave authors time to move patient from OR to angiographic room (not available at the moment in our hospital a hybrid surgical angiographic suite) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and time to find the primary source in a severe and multiple hemorrhagic trauma, with good clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the Japanese system, emergency physicians can be credentialed after performing REBOA three times during residency training 16. A REBOA patient may have their device placed by an emergency medicine physician and definitive treatment provided by interventional radiology without direct involvement of a surgeon 17. Prospective data from the Japan Trauma Data Bank was used to match REBOA patients to propensity score-adjusted non-REBOA patients and they found that patients who received REBOA were three times more likely to die than patients with similar severity of injuries who did not receive REBOA 16.…”
Section: Trainingmentioning
confidence: 99%